At Europe's borders : medieval towns in the Romanian principalities - Rădvan, Laurențiu, 1975-; Cîrdei, Valentin (Leiden : Brill, 2010)
This ambitious work focuses on the emergence and the development of medieval towns in the two Romanian principalities of South-Eastern Europe, Wallachia and Moldavia, from their earliest days, in the 13th century, up to the 16th. It is the only work of its kind in English, but at the same time the first in the field seeking to identify and substantiate common elements between towns in this area of Europe. It also covers Poland, Hungary and the lands south of the Danube. By relying both on various written sources, and on archeological finds, the author addresses several controversial issues, starting from the particulars of urbanization, through an analysis of local institutions, of urban society and economy, and concluding with thorough case studies. The result is a book which shows that medieval towns in the Romanian Principalities, despite being on the outskirts of Europe, were nevertheless part of it.
Part 1, Medieval towns in Central and Eastern Europe -- Part 2, Towns in Wallachia -- Part 3, Towns in Moldavia
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 13.-15. století; středověká města -- Evropa střední a východní -- 13.-15. století; středověká města -- Evropa jihovýchodní -- 13.-15. století; středověká města -- Rumunsko -- 13.-15. století; medieval cities and towns -- Europe, Central and Eastern -- 13th-15th centuries; medieval cities and towns -- Europe, Southeastern -- 13th-15th centuries; medieval cities and towns -- Romania -- 13th-15th centuries; Valašsko (Rumunsko); Wallachia (Romania); e-knihy online; monografie; e-books online; monographs